A Spectrum Decision Scheme for Cognitive Radio Ad Hoc Networks - Alebeed, Hani (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
A Spectrum decision for Cognitive Radio Network (CRN) is able to detect the best of the free channels in the spectrum for Secondary Users (SUs), without causing interference to Primary Users (PUs). The most important issues to be efficiently handled in such networks are the high level of harmful interference to primary users, and the need to find a way to achieve an efficient utilization of available spectrum at the same time. In this work, we propose an efficient scheme, named as Weight Decision Scheme (WDS), which aims to solve the above-mentioned issues. The proposed scheme is based on the primary user activity. It helps to choose the best free channel for a SU, and reducesthe average interference to PUs. WDS improves network performance as it increases the channel utilization and decreases the interference. The achieved improvements in terms of channel utilization were 72.3%, 34.7% and 53.8% compared with Random selection (RD), Best-Fit Channel selection (BFC) and Longest Idle Time Channel selection (LITC) schemes respectively. The improvements in terms of interference were found to be 73.8%, 35.6% and 54.6% compared with the abovementioned schemes respectively. Keywords: Cognitive radio network, interference ration, spectrum utilization, RD, BFC, LITC, WDS

Öz: Birleşim birincil kullanıcılara (PUs) etki etmeden, ikincil kullanıcılar (SUs) için spektrum içindeki en iyi serbest kanalları tespit edebilmek için alınan spektrum karar Kavramsal Radyo Ağı (CRN) içindir. Bu gibi ağlarda verimli bir şekilde elde tutulması gereken en önemli konular şunlardır; birincil kullanıcılara olan zararlı birleşimlerin yüksek seviyesi ve aynı anda mevcut olan spektrumların oranının verimliliğini başarabilmenin yolunu bulma ihtiyacı olmasıdır. Bu çalışmada, yukarıda bahsedilen konuları çözmeyi hedefleyen verimli bir tasarım önerilmiş, Ağırlık Karar Tasarımı (WDS) olarak adlandırılmıştır. Önerilen tasarım birincil kullanıcı aktivitesine dayalıdır. Bu tasarım, SU için en iyi serbest kanalı seçmeye yardım eder ve PU’lara olan girişim ortalamasını azaltır. WDS, kanal oranını arttırdıkça ve birleşimi azalttıkça ağ performansını geliştirmektedir. Kanal oranı açısından başarılan gelişmeler (%72.3, %34.7 ve %53.8) sırasıyla rastgele seçim (RD), en uygun kanal seçimi (BFC) ve en uzun boşta kalan kanal seçimi (LITC) tasarımları ile karşılaştırılmıştır. Birleşim açısından başarılan gelişmeler %73.8, %35.6 ve %54.6 olarak bulundu ve sırasıyla yukarıda belirtilen tasarımlar ile karşılaştırılmıştır. Anahtar Kelimeler: Kavramsal radyo ağı, birleşim oranı, spektrum oranı, RD, BFC, LITC, WDS.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2016. Supervisor: Assoc. Prof. Dr. Muhammed Salamah.
Keywords: Computer Engineering; Cognitive radio networks; Wireless LANs; Software radio; interference ration; spectrum utilization; RD; BFC; LITC; WDS